Developing 2D games with Unity : independent game programming with C# - Halpern, Jared (Apress, 2019)
"Follow a walkthrough of the Unity Engine and learn important 2D-centric lessons in scripting, working with image assets, animations, cameras, collision detection, and state management. In addition to the fundamentals, you'll learn best practices, helpful game-architectural patterns, and how to customize Unity to suit your needs, all in the context of building a working 2D game"--Publisher's website.